REVIEW: PENDEKATAN METABOLOMIK DALAM EKSPLORASI TANAMAN ANTIHIPERTENSI: PROFIL SENYAWA BIOAKTIF DAN PERUBAHAN METABOLIT ENDOGEN - Khoirunnisa, Intan; Patonah (Acta Pharmaceutica Indonesia, 2025)
Metabolomic techniques represent an analytical strategy that supports the discovery of natural product-based drugs, including antihypertensive agents. This article aims to review various metabolomic techniques and approaches used to identify and characterize bioactive compounds in medicinal plants, highlighting two primary strategies: (1) plant metabolite profiling to identify potential bioactive biomarkers, and (2) analysis of endogenous metabolite changes in biological samples from hypertensive models treated with plant-based interventions. Literature was searched through databases such as PubMed and Google Scholar using relevant keywords. This review focuses on analytical methods such as LC-MS, NMR, and HPLC, data processing strategies including PCA, PLS-DA, and OPLS, and the integration of metabolomic techniques in the validation and exploration of plant-derived antihypertensive compounds. The findings demonstrate that metabolomic approaches significantly contribute to accelerating natural drug discovery by identifying biomarkers and elucidating mechanisms of action through related endogenous metabolic pathways.